The hygiene hypothesis for allergy – conception and evolution - Perkin, Michael R; Strachan, David P (Frontiers in Allergy, 2022)
In 1989, a short paper entitled “Hay fever, hygiene and household size” observed that British children from larger families were less likely to develop hay fever and suggested that this could be because early exposure to infection prevents allergy. This sibship size association for hay fever, since replicated many times in Britain and other affluent countries and confirmed by objective measures of atopy, prompted what has come to be known as the “hygiene hypothesis for allergy”, although that term was not specifically used in the 1989 paper. The present paper reviews the historical roots of the “hygiene hypothesis” and charts its development over more than 30 years. Initial scepticism among immunologists turned to enthusiasm in the mid-1990s as the Th1/Th2 paradigm for allergic sensitisation emerged from animal experiments and the concept of “immunological old friends” became popular from the early 2000s. From the late 1990s, observations of reduced allergy risk among children of anthroposophic families and those brought up on farms suggested that the sibship size effects formed part of a broader range of “hygiene-related” determinants of allergy. Children from large families with farming exposure have approximately sixfold reduction in prevalence of hay fever, indicating the potential strength and epidemiological importance of these environmental determinants. During the 21st century, a wide range of specific microbial, environmental and lifestyle factors have been investigated as possible underlying mechanisms, but sadly none have emerged as robust explanations for the family size and farming effects. Thus, while the “hygiene hypothesis” led to a fundamental reappraisal of our relationship with our microbial environment and to the concept that early exposure, rather than avoidance, is beneficial for developing a healthy immune system, the underlying mechanism for variations in allergy prevalence with family size remains, in Churchillian terms, "a riddle wrapped in a mystery inside an enigma".